Magnetic properties of planar nanowire arrays of Co fabricated on oxidized step-bunched silicon templates - SHVETS, IGOR (NANOTECHNOLOGY, 2012)
Planar nanowire (NW) arrays of Co grown on oxidized step-bunched Si(111) templates exhibit room temperature ferromagnetic behaviour for wire widths down to 25 nm. Temperature and thickness dependent magnetization studies on these polycrystalline NW arrays show that the magnetic anisotropy of the NW array is dominated by shape anisotropy, which keeps the magnetization in-plane with easy axis parallel to the wires. This shape related uniaxial anisotropy is preserved even at low temperatures (10 K). Thickness dependent studies reveal that the magnetization reversal is governed by the curling mode reversal for thick wires whereas thinner wires exhibit a more complex behaviour which is related to thermal effects and size distribution of the crystal grains that constitute the NWs.
PUBLISHED
Keywords: NI NANOWIRES; FE; SURFACES; REVERSAL; STRIPES